Monitoring Korosi Discharge Conveyor G pada Tambang Batubara PT GHI di Kabupaten Banjar Provinsi Kalimantan Selatan - Azi Faturahman Fachreza; Elfida Moralista; Zaenal (UNISBA Press, 2023)
Abstract. Conveyor is a conveyance used to move coal from one place to another continuously. The conveyor is supported by a static building structure made of carbon steel. Carbon steel is used because it is strong and resistant to temperature and pressure, but is susceptible to corrosion due to the influence of its environment. This research was conducted to determine the type of corrosion, corrosion control methods, Corrosion Rate, and Remaining Service Life of the conveyor structure.This research uses the thickness reduction measurement method. Measurements are made to determine the actual thickness of the conveyor structure which has a design life of 15 years and a service life of 7 years. The conveyor structure is above ground level, and has a length of 94 meters which is divided into 3 segments and 25 test points. Measurements were taken using a smart sensor ultrasonic thickness gauge TT 130.The type of corrosion that occurs on the conveyor structure is uniform corrosion. The corrosion control method used is a coating method with a three-layer system using Seaguard 5000 as a primary coating, Sherglass FF as an intermediate coating, and Aliphatic acrylic modified polyurethane as a top coating. Corrosion Rates that occur at each test point range from 0.1543 - 0.2843 mm / year which falls into the